(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdfcGM, GdPj gh aj GddZI ddhWF YfO (B.. (3Hd ZjQ GdeNJda GdGLeGY Ydjg HeYfi GJaGb Cgd GddZI bGd aj eMcj GdUMGMs
(3BNQgG (B:s
(3BNQgG(B: (3hjcQg Ch jMQe JQc YeGQI GdOGQ hfMhgG MJi JNQH Ef de jcf GdNQGH CUdM dgG hGdbhd aj GdGLHGQ YdjgG hYOeg ceG eQ (B... (3hgh MQeI eKd gPG GdJVjjY ddeGd aj ZjQ (B... (3hGdMeO ddg ChdG hBNQGs
(3efbhdI Yf fSNI GdeDda, hjdjgG eSGFd ef U (B616 - 624s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis